(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Latvian Environment Agency carry out complex monitoring of Kemeri National Park since 1995. At now 6 lakes are included in this monitoring programme: - 3 bog lakes - Akacis Melnezers and Lake Slokas, Lake Aklais; - shallow and overgrown lagoone lake Kanieris; - hypertrophic Lake Valgums with heavy anthropogenic impact. Lake management plan contains: - the description of the current state o f each lake; - the optimal or required lake for each lake (objectives of management); - factors which influence the lake, especially anthropogenic; action plan to achieve the objectives.